Предмет: Алгебра,
автор: aea71
Упростить выражение
sin
Ответы
Автор ответа:
0
(sina-cosa)(1+sinacosa)/(1+sinacosa)+cosa-sina=sina-cosa+cosa-sina=0
Автор ответа:
0
(sin^3 x - cos^3 x) / (1+sinx*cosx) + cosx - sinx = (sinx - cosx)(sin^2 x + sinx*cosx + cos^2 x) / (1+sinx*cosx) + cosx - sinx = sinx - cosx + cosx - sinx = 0
Похожие вопросы
Предмет: Алгебра,
автор: monikakuborskaya
Предмет: Математика,
автор: fedosenkokseniya
Предмет: Математика,
автор: brawlstar19455
Предмет: Алгебра,
автор: ден55555